Loss of time-delay signature in the chaotic output of a semiconductor laser with optical feedback - Rontani, D; Locquet, A; Sciamanna, M; Citrin, D S (Optics letters, 2007)
We investigate theoretically the possibility of retrieving the value of the time delay of a semiconductor laser with an external optical feedback from the analysis of its intensity time series. When the feedback rate is moderate and the injection current set such that the laser relaxation-oscillation period is close to the delay, then the time-delay identification becomes extremely difficult, thus improving the security of chaos-based communications using external-cavity lasers.